A review of knowledge on Dragonflies and Damselflies in the Regional Nature Reserve “Foce Volturno – Costa di Licola” - Guglielmi, Marina; De Filippo, Gabriele; Elicio, Francesca; Usai, Alessio (BORNH Bulletin of Regional Natural History, 2024)
Based on studies conducted on the Odonata of Campania between the 1980s and 1990s, the Authors have updated the list of species present in the wetlands of the Regional Natural Reserve “Foce Volturno - Costa di Licola”, located between the provinces of Caserta and Naples (Campania, Southern Italy). The compilation of the check-list was conducted through bibliographic research in texts and databases, along with new surveys in the sites and initiating citizen science projects. In total, 22 species were recorded (23.1% of Italian species and 39.2% of Campanian species as of 2022), including 7 belonging to the Damselflies and 15 to the Dragonflies. Referring to the regional Odonate fauna list of 1995, 18 species are confirmed (32.14% of those reported in Campania and 18.9% of those reported in Italy as of 2022). In addition to these, Selysiothemis nigra and Brachytron pratense were sampled by the Authors for the first time in the Reserve area, and Orthetrum trinacria was observed by a citizen scientist for the first time at the regional level, data relevant to their national distribution. The contribution provided brings the total number of Odonata species in Campania to 58 and represents the first piece of an ongoing investigation into species richness at the regional scale.